An alternative way of understanding exit, voice and loyalty: the case of informal payments for health care in Israel. (31st July 2015) - Cohen, Nissim; Filc, Dani
Summary: This study examines Hirschman's model of exit, voice and loyalty with regard to informal payments in the Israeli healthcare system. Based on a national survey, we investigate the extent of "black" payments, its characteristics and its correlated factors. We find that informal payments do exist in Israel—although it seems that there has been a decline in the phenomenon. Contrary to the literature, we find no relationship between the option of voice or dissatisfaction with healthcare services and informal payments. However, we do find a negative correlation between trust and the use of such payments. This finding is consistent with Hirschman's insight that a lack of loyalty may lead people to strategies of exit. We suggest that given the fact that health care in Israel is a public service, the exit option may actually be a quasi‐exit behavior. Copyright © 2015 John Wiley & Sons, Ltd.